Integrating smoking cessation into HIV care settings: A systematic review and meta-analysis of effectiveness and the evidence gap in cost-effectiveness - Van Minh Nguyen; Thanh Hoang; Yesim Tozan; Mikael Svensson; Minh Van Hoang; Nawi Ng (PLoS ONE, 2026)
The prevalence of smoking among people living with HIV (PLWH) is higher than in the general population, and PLWH who smoke are at increased risk of both smoking- and HIV-related comorbidities. As most PLWH reside in low- and middle-income countries (LMICs), there is a need for effective and cost-effective smoking cessation interventions in resource-constrained settings. We systematically reviewed and meta-analyzed the effectiveness of smoking cessation interventions for PLWH and looked for economic evaluations. Four databases (PubMed, Cochrane, Scopus, Web of Science) were searched up to March 23 rd , 2026. Interventional and quasi-experimental studies evaluating smoking cessation interventions for PLWH were included. Risk of bias was assessed using Cochrane’s risk-of-bias tool for randomized studies and the Effective Public Healthcare Panacea Project tool for non-randomized studies. Thirty-two articles met the inclusion criteria. Most evidence originated from high-income countries, with three randomized controlled trials conducted in LMICs (Kenya, South Africa and Vietnam). No economic evaluations were identified. Smoking cessation interventions varied in type, duration, intensity, and mode of delivery. Overall, studies had low to moderate risk of bias. GRADE assessments indicated moderate-certainty evidence that pharmacological interventions (RR 1.86, 95% CI 1.42–2.45) and tailored, intensive behavioral support (RR 1.34, 95% CI 1.05–1.71) increase smoking abstinence compared with standard care. This review indicates that pharmacological and tailored, intensive behavioral support interventions can support smoking cessation among PLWH, including emerging evidence from LMICs, but the absence of economic evaluations limits guidance for resource-constrained settings. Future research should prioritise implementation strategies and economic evaluations to support scalable integration into routine HIV care. (PROSPERO Registration no: CRD42022313630).